2008
DOI: 10.1111/j.1601-5037.2008.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene practices, dental knowledge, dietary habits and their relation to caries among male primary school children in Al Hassa, Saudi Arabia

Abstract: The poor oral hygiene practices, lack of parental guidance and appropriate dental health knowledge with frequent exposure to cariogenic foods in addition to socio-demographics are the main risk factors for dental decay among the surveyed students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 17 publications
8
75
5
2
Order By: Relevance
“…23,24 In our study the prevalence of daily brushing was reported that majority of the students brushed once daily (71.3%), and 82.5% were using toothbrush and toothpaste , while a study conducted by Amin et al in 2008 who reported that 45% of students were using miswak as a brushing tool. 25 With regard to frequency of teeth brushing, our finding is less than other studies [52.6%] which reported twice daily frequency. Most previous studies report a high rate of twice daily or more tooth-brushing.…”
Section: Discussioncontrasting
confidence: 56%
“…23,24 In our study the prevalence of daily brushing was reported that majority of the students brushed once daily (71.3%), and 82.5% were using toothbrush and toothpaste , while a study conducted by Amin et al in 2008 who reported that 45% of students were using miswak as a brushing tool. 25 With regard to frequency of teeth brushing, our finding is less than other studies [52.6%] which reported twice daily frequency. Most previous studies report a high rate of twice daily or more tooth-brushing.…”
Section: Discussioncontrasting
confidence: 56%
“…Diet and eating habits also played an important role for dental caries, in our study a significant association was obtained with milk and rice, usage of these two components gives the protection from caries, and several studies showed a negative association between more intake of milk and rice with and dental caries, a past study gives the evidence that, those non poor children who did not take breakfast daily or ate fewer than five serving of fruits and vegetables per day were found at higher risk of dental caries [6], in our study oral hygiene also gives significant association with dental caries, studies showed bad practice were observed among those children who were found with dental caries [3].…”
Section: Discussionmentioning
confidence: 48%
“…Dental Caries or commonly known as tooth decay is one of the common health problem among child and adults, it is a chronic disease, having a gradual increase of prevalence in the world, study showed that, in USA among children aged from 5-9 years old the prevalence of dental caries was 50% [1], Asian Countries also suffering from this problem, statistics from Pakistan reported day by day in different research journals, a study was conducted in sadder town school children of Karachi city, it gives the prevalence of dental carries among school going children was 51% [2], if we looked at international levels among Muslim countries, Iran, UAE and Saudi Arabian Childs also victim of this public health problem, a study conducted in Saudi Arab showed 68.9% tooth decayed among school going children's [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tooth cleaning with the brush is at the age of two years are rare among children and the age of brushing their teeth is beginning after three years of maturation [29][30][31]. Oral hygiene care practices in the Saudi population seem to start later than the suggested time for the teeth cleaning.…”
Section: Oral Hygiene Practicesmentioning
confidence: 99%